The Corruption Cure : How Citizens and Leaders Can Combat Graft - Rotberg, Robert I. (Book collections on Project MUSE., 2017)
"Corruption corrodes all facets of the world's political and corporate life, yet until now there was no one book that explained how best to battle it. The Corruption Cure provides many of the required solutions and ranges widely across continents and diverse cultures--putting some thirty-five countries under an anticorruption microscope--to show exactly how to beat back the forces of sleaze and graft. Robert Rotberg defines corruption theoretically and practically in its many forms, describes the available legal remedies, and examines how we know and measure corruption's presence. He looks at successful and unsuccessful attempts to employ anticorruption investigative commissions to combat political theft and venal behavior. He explores how the globe's least corrupt nations reached that exceptional goal. Another chapter discusses the role of civil society in limiting corruption. Expressed political will through determined leadership is a key factor in winning all of these battles. Rotberg analyzes the best-performing noncorrupt states to show how consummate leadership made a telling difference. He demonstrates precisely how determined leaders changed their wildly corrupt countries into paragons of virtue, and how leadership is making a significant difference in stimulating political anticorruption movements in places like India, Croatia, Honduras, and Lebanon. Rotberg looks at corporate corruption and how it can be checked, and also offers an innovative fourteen-step plan for nations that are ready to end corruption. Curing rampant corruption globally requires strengthened political leadership and the willingness to remake national political cultures. Tougher laws and better prosecutions are not enough. This book enables us to rethink the problem completely--and solve it once and for all."--